Telenursing Using SKEDit To Educate Parents with Thalassemia Children - Andodo, Candra; Haryanti, Fitri; Widyandana, Widyandana (Jurnal Keperawatan Soedirman, 2019)
Background: Excess iron levels and low hemoglobin (Hb) levels are one of the complications of Beta-Thalassemia. The implementation of education using WhatsApp is expected to increase parental knowledge of the illness and children to adhere to iron chelation therapy. Objective: To identify the effect of the implementation of education using WhatsApp through the SKEDit application compared to using booklets on parental knowledge and medication adherence in pediatric patients with thalassemia. Method: The study was quasi-experimental using pre and post-test with control group.  The total sample was 61 respondents with purposive sampling technique. Parental knowledge was measured using a Parental knowledge about Thalassemia questionnaire and the level of adherence was measured using an indirect method known as 'Pill Count'. The data were then analyzed using the Mann whitney and wilcoxon test. Results: There was a significant difference in the level of knowledge in the pretest and posttest on the intervention group (p: 0.001) and the pretest and posttest in the control group (p: 0.001). There was a significant difference in the level of adherence of the pretest and posttest in the intervention group (p: 0.028). There was no significant difference in the level of adherence of the pretest and posttest in the control group (p: 0.214). There was no difference in the level of knowledge between the two groups (p: 0.994). There was no difference in the level of adherence between the two groups (p: 0.987). Conclusion: Providing education using WhatsApp through the SKEDit application and also booklets both effectively increase the level of parental knowledge and medication adherence of pediatric patients with thalassemia.